A General Range-Velocity Processing Scheme for Discontinuous Spectrum FMCW Signal in HFSWR Applications - Mengguan Pan; Baixiao Chen; Minglei Yang (International Journal of Antennas and Propagation)
Discontinuous spectrum signal which has separate subbands distributed over a wide spectrum band is a solution to synthesize a wideband waveform in a highly congested spectrum environment. In this paper, we present a general range-velocity processing scheme for the discontinuous spectrum-frequency modulated continuous wave (DS-FMCW) signal specifically. In range domain, we propose a simple time rearrangement operation which converts the range transform problem of the DS-FMCW signal to a general spectral estimation problem of nonuniformly sampled data. Conventional periodogram results in a dirty range spectrum with high sidelobes which cannot be suppressed by traditional spectral weighting. In this paper, we introduce the iterative adaptive approach (IAA) in the estimation of the range spectrum. IAA is shown to have the ability to provide a clean range spectrum. On the other hand, the discontinuity of the signal spectrum has little impact on the velocity processing. However, with the range resolution improved, the influence of the target motion becomes nonnegligible. We present a velocity compensation strategy which includes the intersweep compensation and in-sweep compensation. Our processing scheme with the velocity compensation is shown to provide an accurate and clean range-velocity image which benefits the following detection process.